Unity in diversity? When advocacy coalitions and policy beliefs grow trees in South Africa. (March 2021) - Malkamäki, Arttu; Ylä-Anttila, Tuomas; Brockhaus, Maria; Toppinen, Anne; Wagner, Paul M.
Highlights: Coalition formation inside South African tree plantation politics is analysed. Interviews with organisational elites to determine the contributions of different types of policy beliefs to coalition formation. Based on shared core beliefs, a "business-as-usual" coalition and a "justice and change" coalition are identified. Abstract: Competing coalitions can stabilise policymaking and hinder policy changes that are required to address the mounting pressures on land use systems across the globe. Thus, understanding the driving forces of coalition formation is important. This paper builds on the Advocacy Coalition Framework to determine the relative contributions of two sets of beliefs (more general policy core beliefs and more specific beliefs concerning policy instruments) to coalition formation in South African tree plantation politics and to identify coalitions therein. Discourse Network Analysis was used to code 656 statements regarding 40 beliefs to create network data from 55 interviews with organisational elites. Results from a network analysis of the twelve most salient beliefs indicate that dissimilar policy core beliefs about the validity of environmental regulation, social costs of tree plantations, and the conditionality of land reform in South Africa divide actors into two coalitions: the hegemonic "business-as-usual" coalition and the minority "justice and change" coalition. These boundaries were confirmed by comparing the network based on shared policy core beliefs with a co-ordination network. Dissimilar beliefs concerning policy instruments, including eco-certification and an indicative zoning, also divide actors, yet actors' reasoning for or against these instruments differ to the degree that united fronts are unlikely to form. Hegemonic coalitions that combine selected state and business interests with labour arguments and prioritise short-term economic efficiency threaten to delay the necessary changes away from business-as-usual across land use systems in South Africa and beyond.